DEVELOPMENT OF BUSY BOARD MEDIA ON FINE MOTOR ABILITIES OF 4-5 YEAR OLD CHILDREN - Durotun Nikmah; Rista Sundari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research is motivated by the problem of limited varied learning media in the institution and the less than optimal fine motor skills of children in a group A. This can be seen from writing activities that still require teacher assistance, coloring outside the lines, and cutting not according to the pattern. The purpose of this study is to develop and test the effectiveness or level of feasibility of Busy Board media in improving children’s fine motor skills. The research method uses the ADDIE model approach which consists of five stages including Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 14 children in group A with data collection techniques through pre-test (before) and post-test (after) while data analysis used quantitative descriptive research techniques. Based on the trials that have been conducted, Busy Board media is effective in improving aspects of child development, especially in fine motor aspects. This can be seen in the post-test results showing high scores after the pre-test on the five Busy Board activities. Busy Board media not only improves fine motor skills but also multi-aspects. Matching geometric shapes and counting buttons on the train improved children’s cognitive abilities with a score of 3,8. The highest score was achieved in singing with a microphone with a score of 3,9, which improved language and art skills. Researchers encountered obstacles in the field. Such as tying shoelaces due to daily habits. Another obstacle was the name of the activity, which was lost due to the use of glue that did not stick well, so researchers began to revise the shortcomings of the media. Busy Board successfully overcomes the limitations of educational play tools and can improve children’s fine motor skills.